Penerapan Prinsip Arsitektur Hijau pada Lumbung Padi Vernakular Kasepuhan Gelar Alam - Sukabumi, Indonesia: Warisan Kearifan Lokal yang Berkelanjutan - Kusumawardhani, Seruni (Program Studi Desain Interior Unikom, 2024)
This research examines the application of green architecture principles in preserving and revitalizing vernacular rice granaries in Indonesia, focusing on a case study in Kasepuhan Gelar Alam, Halimun Mountain National Park, Sukabumi Regency, West Java. Kasepuhan Gelar Alam, established in 2023, is a result of relocation from Kasepuhan Ciptagelar, continuing the 'ngalalakon' tradition that has been ongoing since 1368. The rice granaries, or 'leuit' in the Sundanese language, are the main object of this study, given their vital role in the life of the local community. This research employs a qualitative method with an ethnographic approach, involving three main stages: data collection through participatory observation, interviews, and documentation; processing and analysis focusing on applying six green architecture principles to the leuit. These principles include (1) energy conservation, (2) climate adaptation, (3) minimizing new resource use, (4) respect for users, (5) respect for site, and (6) a holistic approach. The final stage involves drawing conclusions based on the results of the analysis. The main focus of the research is Leuit Si Jimat, which serves as a reference for all rice granaries in Kasepuhan Gelar Alam. The research findings indicate that although the architecture of rice granaries in Kasepuhan Gelar Alam is based on customary regulations and ancestral culture, modern green architecture principles are applied in their design and construction. This finding highlights the potential integration between green architecture and cultural heritage preservation, opening opportunities for developing sustainable strategies in preserving and revitalizing similar vernacular structures throughout Indonesia. Keywords: green architecture, rice granary, leuit, Kasepuhan Gelar Alam, cultural preservation, sustainability